PERANAN BEBERAPA JENIS TANAMAN HUTAN KOTA DALAM PENGURANGAN DAMPAK EMISI LOGAM BERAT DI UDARA - Gusmailina Gusmailina (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
The increase of motorized vehicles in the city has caused environment problems, especially the air pollution as the emission of gasses containing heavy metals such as Pb endangers. Therefore the selected of tree city forest based on environmental benefit management must be necessary to criteria development forest city programme.This article presents some result of absorption and adsorption of Pb heavy metals by several plants. The results showed the Cinnamonunum sp more effective to adsorp the Pb heavy metals in the air, furthere more Agatliis lorantifolia, Paraserianthes falcataria, and Swietenia macrophylla. Whereas Agathis lorantifolia more effectiveto absorp the Pb heavy metals in the air, furthere more Swietenia macrophylla, Paraserianthes falcataria, and Cinnamornmum sp.Keywords : Environment, Pb heavy metal, Absorption, Adsorption, Urban forest.